Leveraging digital capabilities toward a circular economy: Reinforcing sustainable supply chain management with Industry 4.0 technologies. (April 2023) - Liu, Lingdi; Song, Wenyan; Liu, Yang
Abstract: Facing the challenges of globalisation and unpredictable shocks, manufacturers seek novel methods to maintain the sustainability of their supply chains. Adopting Industry 4.0 (I4.0) technologies facilitates sustainable supply chain management (SSCM) with the precise decision-making of supply chain activities and the realisation of circular development. However, according to the bibliometric analysis and systematic literature review of articles related to "SSCM", few frameworks with I4.0 technologies are found to empower SSCM under circular economy (CE) logic. Thus, this article proposes a conceptual framework of I4.0 technologies-embedded SSCM, which takes advantage of five kinds of emerging digital technologies, including cloud services, artificial intelligence (AI), big data analytics (BDA), blockchain technology (BT), and internet of things (IoT). The CAB 2 IN framework is based on the technologies mentioned above alongside the design, manufacturing, delivering, using, and end-of-life stages of products and services to meet the requirements of reducing material usage, remanufacturing, reusing, and recycling. This paper's contribution lies in indicating the trends of SSCM in the era of Industry 4.0 and proposing CAB 2 IN to creatively establish the virtual side of circular SSCM, which leverages the data generated in each stage to assist sustainable decision-making. CAB 2 IN illuminates several research directions for future studies of digitalised SSCM under the perspective of CE. The case of Company S illustrates the application of CAB 2 IN in the healthcare supply chain. This paper also summarises insightful directions of digitalised SSCM under the proposed circular framework. Highlights: Emerging technologies in SSCM are identified with bibliometric analysis. A framework integrating information and digital technologies in SSCM is developed. The framework guides the lifecycle management of SSCM with digital technologies. A case study of pharmaceutical SSCM is used to validate the proposed framework.